TECHNOLOGICAL ADVANCEMENTS IN ACCOUNTING: HOW COMPUTERIZED SYSTEMS ARE CHANGING OIL AND GAS BUSINESSES IN PORT HARCOURT - Eze, Ngozi Chiamaka; Obi, Uchechukwu Festus (International Research Journal of Arts and Communication, 2024)
The rapid advancement of Information and Computer Technologies (ICTs) has become indispensable in contemporary societies, permeating all aspects of human activities. Information technology, which includes hardware, software, and IT controls, has revolutionized organizational operations, transforming the way tasks are performed and decision-making processes are supported. CAS refers to an accounting information system that processes financial transactions according to Generally Accepted Accounting Principles (GAAP) with the assistance of computers or automated devices. However, despite the widespread adoption of CAS, there remains a need to assess its impact on organizational performance, particularly in specific sectors such as the oil and gas industry. This study aims to examine the effect of computerized accounting systems on the organizational performance of oil and gas firms in Port Harcourt, Nigeria. Previous research in Nigeria has primarily focused on AIS in general or specific industries, such as deposit money banks, manufacturing companies, microfinance banks, and SMEs. Therefore, the study seeks to fill the gap in literature by investigating the impact of CAS on oil and gas firms' performance, specifically in terms of accountability, productivity, and cost control. The findings of this study will contribute to a better understanding of the relationship between CAS and organizational performance, providing insights for practitioners, policymakers, and researchers in the oil and gas industry. Ultimately, this research endeavors to facilitate informed decision-making regarding the adoption and optimization of computerized accounting systems in the oil and gas sector, thereby enhancing overall organizational performance.